Consistent Biofilm Formation by Streptococcus pyogenes emm 1 Isolated From Patients With Necrotizing Soft Tissue Infections - Skutlaberg, Dag Harald; Wiker, Harald G.; Mylvaganam, Haima; , The INFECT Study Group; Norrby-Teglund, Anna; Skrede, Steinar (Frontiers in Microbiology, 2022)
Objectives: Biofilm formation has been demonstrated in muscle and soft tissue samples from patients with necrotizing soft tissue infection (NSTI) caused by Streptococcus pyogenes, but the clinical importance of this observation is not clear. Although M-protein has been shown to be important for in vitro biofilm formation in S. pyogenes, the evidence for an association between emm type and biofilm forming capacity is conflicting. Here we characterize the biofilm forming capacity in a collection of S. pyogenes isolates causing NSTI, and relate this to emm type of the isolates and clinical characteristics of the patients. Methods: Bacterial isolates and clinical data were obtained from NSTI patients enrolled in a multicentre prospective observational study. Biofilm forming capacity was determined using a microtitre plate assay. Results: Among 57 cases, the three most frequently encountered emm types were emm1 (n = 22), emm3 (n = 13) and emm28 (n = 7). The distribution of biofilm forming capacity in emm1 was qualitatively (narrow-ranged normal distribution) and quantitatively (21/22 isolates in the intermediate range) different from other emm types (wide ranged, multimodal distribution with 5/35 isolates in the same range as emm1). There were no significant associations between biofilm forming capacity and clinical characteristics of the patients. Conclusions: The biofilm forming capacity of emm1 isolates was uniform and differed significantly from other emm types. The impact of biofilm formation in NSTI caused by S. pyogenes on clinical outcomes remains uncertain.